LATCHES - a memory aide for the principles of attachment for effective breastfeeding: findings of a regional pilot in the Northeast of England and North Cumbria - Lynette Harland Shotton; Cheryl Elliot; Roslyn Nunn; Kathryn Lane (BMC, 2024)
Abstract Background This paper outlines a pilot of a new memory aide for breastfeeding conducted in the Northeast of England and North Cumbria between April and August 2023. The United Kingdom has some of the lowest rates of breastfeeding, particularly in the Northeast of England, and as such more needs to be done to support mothers to breastfeed for as long as they would like to. Good support from health professionals can be effective in influencing decisions to breastfeed as well as helping to ensure initiation and continuation of breastfeeding but there is evidence to suggest that professionals and students do not always feel adequately trained and it is here, where memory aides may have value. Methods Key breastfeeding practitioners and educators were brought together to select one of two memory aides for principles of attachment for effective breastfeeding. The selected memory aide, LATCHS, was piloted with 57 participants with a key role in promotion and support of breastfeeding in the Northeast of England and North Cumbria. Results Participants conveyed mixed views about the proposed memory aide with more experienced staff reporting more favourable opinions than student midwives and early years practitioners. Experienced staff felt the new memory aide would complement an early memory aide, CHINS, which focused on principles of positioning. Discussion Findings of the pilot indicate there is a role for a mnemonic to help practitioners understand, recall, and retain theory around attachment for effective breastfeeding and that memory aides can play an important role in complementing existing approaches to education and practice. The participants felt the proposed memory aide had some limitations and suggested important ways for it to be improved, particularly in adding an E to reflect the expecting wording. This produced the final memory aide: LATCHES. Conclusion Using data from the pilot, the memory aide was refined, and the final version LATCHES agreed for wider dissemination. Future research is needed to understand the value of LATCHES on the wider breastfeeding workforce and whether any future improvements can be made to enhance its utility.